National Housing Policies and the Realisation of Improved Housing for All in Nigeria: An Alternative Approach - E, Kalu Ijeoma; Ugochukwu, Agbarakwe Henry; F, Anowor Oluchukwu (Asian Development Policy Review, 2014)
The seventh goal of the MDGs is to ensure environmental sustainability which includes as its targets: increasing access to new technologies to support sustainable development by making information about sustainable practices more widespread, and bringing new technologies to rural areas such that people will be able to have better access to information and employment without having to migrate to urban areas; these would without doubt help to system the flow of rural-urban migration and as well stem the growth of slums. Good quality housing as a basic need is lacking for a sizeable number of people around the globe but seem most severe in developing economies including Nigeria. Also few houses are available, especially in the urban centers, to the ever increasing number of workers in both formal and informal sectors. The debates on the direction of housing and welfare policy have often been guided by assumptions derived from a preponderance of Anglo-American cases and perspectives. The purpose of this study is to present an alternative approach to housing policies especially in Nigeria; and we have come to the inescapable conclusion that housing is a social responsibility which cannot be left to the free play of market forces. This study therefore recommends the need to strengthen institutions and overhaul systems and processes for a more virile housing sector such that a balance between the urban housing units and the rural housing units could be attained.